The Role of Tissue-Nonspecific Alkaline Phosphatase in Dental Tissue: A Review of Recent Literature - Graser, Stephanie; Riekert, Elisa; Liedtke, Daniel (Osteologie, 2022)
This brief review describes the role of tissue-nonspecific alkaline phosphatase (TNAP) during dental development. Mutations within the ALPL gene, which is encoding the human ectoenzyme TNAP, lead to the rare disease Hypophosphatasia (HPP). Apart from the most prominent bone hypomineralization, the characteristic symptoms of HPP often include a dental phenotype. To investigate the molecular causes of distinct HPP symptoms in closer detail, a number of transgenic models in different animals are established, like mice (Mus musculus) and zebrafish (Danio rerio). We therefore also compare the processes of dental development in humans, mice, and zebrafish.
Keywords: Hypophosphatasia; TNAP; dental; zebrafish; mouse